Is primary dysmenorrhea a precursor of future endometriosis development?. (3rd April 2021) - Clemenza, Sara; Vannuccini, Silvia; Capezzuoli, Tommaso; Meleca, Chiara Immacolata; Pampaloni, Francesca; Petraglia, Felice
Abstract: Primary dysmenorrhea (PD) is the most common gynecologic disorder during adolescence and it is characterized by crampy lower abdominal pain that occurs during menstruation. Secondary dysmenorrhea, in contrast, has the same clinical features but occurs in women with a disease that could account for their symptoms (endometriosis, adenomyosis, uterine fibroids, pelvic inflammatory disease). Endometriosis is the most common cause of secondary dysmenorrhea and it should be considered in patients with persistent and clinically significant dysmenorrhea despite treatment. It is often diagnosed after a long delay, increasing the likelihood of pain chronicity and fertility problems at a later age. Women who suffer from dysmenorrhea in adolescence have higher risk of endometriosis in future. The open question is if endometriosis was already present at the onset of dysmenorrhea but undiagnosed or if PD favors subsequent development of endometriosis-associated pain. Since PD is associated with higher risk for developing chronic pain state and shares some of the same pain pathways of endometriosis (prostaglandins overproduction, inflammation, peripheral sensitization, central sensitization and abnormal stress responses), a correlation between PD and endometriosis is suggested. To know whether it is a risk factor for the development of endometriosis-associated pain may provide an opportunity for early intervention and prevention. The present review aims to investigate the clinical and pathogenetic features of PD and endometriosis in order to identify a possible association between the two conditions.